Evolution of outcomes for patients hospitalised during the first 9 months of the SARS-CoV-2 pandemic in France: A retrospective national surveillance data analysis - Noémie Lefrancq; Juliette Paireau; Nathanaël Hozé; Noémie Courtejoie; Yazdan Yazdanpanah; Lila Bouadma; Pierre-Yves Boëlle; Fanny Chereau; Henrik Salje; Simon Cauchemez (Elsevier, 2021)
Background: As SARS-CoV-2 continues to spread, a thorough characterisation of healthcare needs and patient outcomes, and how they have changed over time, is essential to inform planning. Methods: We developed a probabilistic framework to analyse detailed patient trajectories from 198,846 hospitalisations in France during the first nine months of the pandemic. Our model accounts for the varying age- and sex- distribution of patients, and explore changes in outcome probabilities as well as length of stay. Findings: We found that there were marked changes in the age and sex of hospitalisations over the study period. In particular, the proportion of hospitalised individuals that were >80y varied between 27% and 48% over the course of the epidemic, and was lowest during the inter-peak period. The probability of hospitalised patients entering ICU dropped from 0·25 (0·24-0·26) to 0·13 (0·12-0·14) over the four first months as case numbers fell, before rising to 0·19 (0·19-0·20) during the second wave. The probability of death followed a similar trajectory, falling from 0·25 (0·24-0·26) to 0·10 (0·09-0·11) after the first wave before increasing again during the second wave to 0·19 (0·18-0·19). Overall, we find both the probability of death and the probability of entering ICU were significantly correlated with COVID-19 ICU occupancy. Interpretation: There are large scale trends in patients outcomes by age, sex and over time. These need to be considered in ongoing healthcare planning efforts. Funding: INCEPTION.